Saint Augustine & the fall of the soul : beyond O'Connell & his critics - Rombs, Ronnie J. (Catholic University of America Press, 2006)
"Saint Augustine and the Fall of the Soul: Beyond O'Connell and His Critics provides first a critical examination of O'Connell's theses in a readable summary of his work that spanned over thirty years. Secondly, a diachronic study of Augustine's writings traces the development of his understanding of the soul's fall, mapping the limits of Plotinus's influence."--Jacket.